Changes in the Functional Components of Barley Produced from Different Cultivars and Germination Periods. Issue 6 (15th August 2017) - Lee, Yoon Jeong; Jang, Gwi Yeong; Li, Meishan; Kim, Min Young; Kim, Eun Hee; Lee, Mi Ja; Lee, Junsoo; Jeong, Heon Sang
Abstract : This study investigated the changes in the functional components of three cultivars (Kunalbori, Dahan, and Hinchalssalbori) over a 6 day germination period; these cultivars were selected because of their varied characteristics and applications. Barley produced from the cultivars was subjected to 6 days of germination. Germinated barley was analyzed for total polyphenol, total flavonoid, hordenine, total arabinoxylan, soluble arabinoxylan, γ‐aminobutyric acid, and γ‐oryzanol contents. The total polyphenol content increased with germination period, corresponding to 1.47–3.83, 1.41–3.42, and 1.59–2.82 mg/g in barley produced from the three cultivars, respectively. The corresponding total flavonoid contents were 0.35–0.44, 0.31–0.48, and 0.22–0.37 mg/g. The hordenine contents in the barley produced from the three cultivars increased from not detected for nongerminated barley to 1.52, 1.09, and 1.34 mg/100 g, respectively, at germination day 6. The γ‐aminobutyric acid content significantly increased until germination day 4, followed by a decrease, and the highest content was observed for barley produced from the Kunalbori cultivar at germination day 4. The total arabinoxylan and soluble arabinoxylan contents increased with germination period. Results indicated that the germination period is crucial for increasing the functional components. These results are expected to be beneficial during food product manufacturing.